Aplikasi Paclobutrazol Melalui Daun Tanaman Ubi kayu (Manihot esculenta Crantz.) untuk Merangsang Pembungaan Dini di Dataran Rendah - Yuliadi, Erwin; Sunyoto, Sunyoto; Artika, Kristina; Ardian, Ardian (Jurnal Penelitian Pertanian Terapan, 2012)
The main obstacle in breeding cassava plant is a flowering plant age which is not the same between the genotypes and the long time needed for a breeder to get cassava flowering before it is crossed. The purpose of this study was to determine the application of various concentrations of Paclobutrazol through the leaves of cassava plants to induce early flowering in the lowlands. Plant materials in the form of cuttings were taken with the size of 25 cm in length. The clone used was called Thailand taken from the field 10-12 months after planting. This experiment was conducted with complete randomized block design. Each treatment was repeated three times and each experimental unit consists of at least two-plant samples. Paclobutrazol treatment consisted of a wide range of concentration. Those were: 0 (P0), 250 (P1), 500 (P2), 750 (P3), and 1000 (P4) ppm. Paclobutrazol was sprayed through the leaves and carried out on plants that have been 30 days after planting with a volume of 100 ml per crop. The application through the soil was also done once while through the leaf was done 3 times with 1 week interval, each application was given with a volume of 20 ml, 30 ml and 50 ml. The results showed that Paclobutrazol Application of 500 ppm through the leaf was s the best concentration in stimulating the formation of branches and flowers compared with other Paclobutrazol concentrations Keywords: Paclobutrazol, Cassava Plant, Early Flowering, Lowland